Evaluation of Colony Characteristics and Enzymatic Activity of some Fungi for Potential use in Co-culture for Bio Pulping - Albert, Susy; Pandya, Bhavika; Padhiar, Amee (Asian Journal of Biological and Life Sciences, 2012)
The mycelial growth and colony characteristics of ten fungal isolates grown on Potato Dextrose Agar (PDA) medium were observed after seven days of inoculation at 25 ± 10C. The colony characteristic features appeared to be typical and varied with the species which is presented in the present study. The ten fungal isolates have been screened for its ligninolytic; cellulolytic and xylanolytic activity. Results show 4 of the fungal isolates to be lignin degraders as well as xylanase producers indicating its potential applications in paper industry for bio-bleaching process. Three species of Pleurotus and Phellinus pectinatus are selective lignin degraders having its application in bio-pulping. The two species of Trichoderma are ligninolytic as well as cellulolytic and xylanolytic. Pleurotus sajorcaju showing ligninolytic and xylanolytic activity it was selected for co-culture experiments and found to be compatible with Daedaleopsis confragrosa and Phellinus pectinatus.